Aversion and erasure : the fate of the victim after the Holocaust - Dean, Carolyn J. (Carolyn Janice), 1960- (Cornell University Press, 2010)
In Aversion and Erasure, Carolyn J. Dean offers an account of how the Holocaust's status as humanity's most terrible example of evil has shaped contemporary discourses about victims in the West. Dean explores the pervasive idea that suffering and trauma in the United States and Western Europe have become central to identity, with victims competing for recognition by displaying their collective wounds. She argues that this notion has never been examined systematically even though it now possesses the force of self-evidence. --From publisher's description.